TIC et accès des ruraux à l’information - Ibrahima Sylla (Netcom)
Senegalese farmers are often isolated from any elemental information on the markets and find themselves unable to adapt their production to these places of commercialization. Until then, existing devices gave for instance through the radio a weekly information about the markets prices ie. with a frequency unadapted to the daily variation of those prices. This situation explains their increasing marginalisation inside their production sectors and the development of the informal, since this one deals much better the access to information. But since the informal sector does hardly create material value in the farming industries, those ones encounter a drop of performance that has consequences on the income level of small producers. To solve the problem and to bring the producers closer to their markets and to those in charge of supporting them in their processes, the company Manobi Senegal has implemented an information system on the markets in wolof called Xam Marsé which is made not only to break farmers isolation by a simple mean of access to strategic information, but also to re-up their incomes level.